Silence, Abuse, and Madness: Picasso in Jeanette Winterson’s Art & Lies - Martori, Claudia (The Grove - Working Papers on English Studies, 2023)
In Art & Lies (1994), Jeanette Winterson presents three characters who are alter egos of Handel, Picasso, and Sappho. This article focusses on Picasso as an alter ego not only of Pablo Picasso but also of the character itself, whose birth name is Sophia, and of Pablo Picasso’s lovers, who were silenced, abused, and driven to madness like Winterson’s Picasso. The main aspects taken into account are the fact that the character is silenced by her family and that she is sexually abused by her brother in order to understand that her journey towards becoming the madwoman in the attic is induced by the harmful context that she is surrounded by in the same way that occurred to Pablo Picasso’s lovers and to Bertha Mason in Jane Eyre.